Development of biodegradable PLA composites and tangerine peel flour with improved toughness containing a natural-based terpenoid - Jaume Gomez-Caturla; Nestor Montanes; Luis Quiles-Carrillo; Rafael Balart; Daniel Garcia-Garcia; Franco Dominici; Debora Puglia; Luigi Torre (eXPRESS Polymer Letters, 2023)
The present work reports on the development of environmentally friendly, completely biodegradable wood plastic composites based on polylactide (PLA) and tangerine peel flour (TPF), plasticized by α-terpinyl acetate (TA). The TPF varied in the 10–30 wt% while the PLA to TA (wt%/wt%) was set to 4 (i.e., 25 wt% TA plasticizer was added with regard to the PLA wt%). The developed composites were processed by extrusion and injection molding. The composites presented excellent elongation at break, achieving values of 300% for the PLA+TA sample. Elongation at break values of 200% for the PLA composite with 10 wt% TPF and plasticized with TA were obtained. Those results were confirmed by the appearance of filament-like structures observed in field emission scanning electron microscopy images. Differential scanning calorimetry and dynamic mechanical thermal analysis revealed a remarkable decrease in the glass transition temperature of PLA as a result of the plasticizing effect of TA. Glass transition was reduced from 63°C down to 41°C approximately. This implied an increase in the ductility of the material. The samples with TPF exhibited a dark brown color, making them perfect for wood plastic composite applications. Water contact angle results show that TA and TPF change the wetting properties of the obtained composites. A general decrease in the water contact angle was observed with the addition of TPF and TA. Finally, disintegration tests proved that the developed composites are fully biodegradable. All the samples except for neat PLA achieved 100% disintegration in controlled compost soil conditions after 5 weeks, while neat PLA reached complete disintegration in 6 weeks.